Column packing material, column for liquid chromatography, and method of producing column for liquid chromatography
The use of spherical porous glass beads with specific compositions and surface modifications addresses the mechanical and adsorption limitations of silica gel, enabling high-pressure liquid chromatography with improved separation and retention capabilities.
Patent Information
- Application Number
- JP2024097540
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2024-06-17
- Publication Date
- 2025-01-20
AI Technical Summary
Silica gel used in liquid chromatography columns often has low mechanical strength due to partial cutting of siloxane bonds, complicates manufacturing with additional adsorption capacity requirements, and has limited adsorption points for organic compounds.
A column packing material composed of substantially spherical porous glass beads with specific glass compositions and surface modifications, including hydrophobic functional groups, providing high mechanical strength, good pore characteristics, and adsorption ability for specific organic compounds.
The solution results in a column packing material with enhanced mechanical strength, improved pore characteristics, and adsorption capacity for organic compounds, suitable for high-pressure liquid chromatography applications.
Smart Images

Figure 2025009918000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a column packing material, a liquid chromatography column, and a method for producing a liquid chromatography column. [Background technology]
[0002] Silica gel prepared by the sol-gel method is widely used as a column packing material. In addition, porous glass beads prepared by a phase separation method for use as a column packing material have been reported (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2023-26324 A Summary of the Invention [Problem to be solved by the invention]
[0004] In liquid chromatography columns, silica gel is used as a column packing material. Silica gel produced by the sol-gel method often has some siloxane bonds in the silica skeleton broken, which tends to reduce the mechanical strength of the column packing material. In addition, the sol-gel method has a large number of factors that affect the pore characteristics (e.g., composition, type and amount of solvent, type of catalyst, gelation conditions, aging conditions, drying conditions, etc.), making it difficult to obtain a sharp pore distribution, which may affect the separation characteristics of liquid chromatography columns. Furthermore, there are few adsorption points on the surface of silica gel that strongly adsorb organic compounds. Therefore, if it is desired to impart adsorption ability (meaning that compounds are adsorbed in the column and not eluted) in addition to the retention and separation ability of organic compounds, it is necessary to additionally introduce organic modification groups with adsorption ability, which complicates the manufacturing process of the column packing material.
[0005] In view of the above, an object of the present invention is to provide a column packing material which has high mechanical strength, good pore characteristics and solid acidity, and which has an adsorption ability for specific organic compounds in addition to an ability to retain and separate organic compounds, a liquid chromatography column, and a method for producing a liquid chromatography column. [Means for solving the problem]
[0006] The following describes various aspects of a column packing material, a liquid chromatography column, and a method for producing a liquid chromatography column that solves the above problems.
[0007] The column packing material of the first aspect is characterized in that it has a breaking strength of 0.1 GPa or more and is made of approximately spherical porous glass beads.
[0008] In the column packing material of the second aspect, in the first aspect, the porous glass beads preferably contain SiO2 and ZrO2 as a glass composition.
[0009] The column packing material of Aspect 3 is preferably such that in Aspect 1 or Aspect 2, the porous glass beads contain, in mass %, as a glass composition, 70 to 95% SiO2, more than 0 to 25% ZrO2, 0 to 10% Al2O3, and 0 to 10% B2O3 + Na2O + K2O + CaO + P2O5 + TiO2.
[0010] In the column packing material of Aspect 4, in any one of Aspects 1 to 3, the porous glass beads preferably contain, in mass %, 10 to 25% ZrO2 as a glass composition.
[0011] The column packing material of embodiment 5 is, in any one of embodiments 1 to 4, the average particle diameter D 50 It is preferable that the diameter of the porous layer is 0.1 to 300 μm and the pore size is 1 to 1000 nm.
[0012] A column packing material according to a sixth aspect of the present invention is a column packing material according to any one of the first to fifth aspects, in which the specific surface area of the porous glass beads is 10 to 800 m 2 It is preferred that the molecular weight is / g.
[0013] The column packing material of embodiment 7 is, in any one of embodiments 1 to 6, the half width Δd and the mode diameter d in the pore size distribution of the porous glass beads. m The ratio Δd / d m It is preferable that the ratio is 0.55 or less.
[0014] The column packing material of embodiment 8 is any one of embodiment 1 to embodiment 7, wherein at least a part of the inner surface of the pores of the porous glass beads is modified with a hydrophobic functional group.
[0015] In the column packing material of Aspect 9, in Aspect 8, the hydrophobic functional group is preferably an octadecylsilyl group and / or a trimethylsilyl group.
[0016] The column packing material of Aspect 10, in any one of Aspects 1 to 9, is preferably used for liquid chromatography.
[0017] A liquid chromatography column according to an eleventh aspect of the present invention is characterized in that it comprises a column housing and the column packing material according to any one of the first to tenth aspects packed in the column housing.
[0018] The liquid chromatography column of the twelfth embodiment is preferably a reverse phase liquid chromatography column in the eleventh embodiment.
[0019] The manufacturing method of a liquid chromatography column of embodiment 13 includes a precursor preparation step of obtaining precursor particles by crushing a glass base material, a porosification step of heat-treating the precursor particles to separate them into two phases, and then removing one of the phases with an acid to obtain porous glass beads, a surface modification step of performing surface modification using a silane coupling agent, and a filling step of filling a column housing with the porous glass beads, wherein the porous glass beads are characterized by having a breaking strength of 0.1 GPa or more and being approximately spherical. Effect of the Invention
[0020] According to the present invention, it is possible to provide a column packing material which has high mechanical strength, good pore characteristics and solid acidity, and which has an adsorption ability for specific organic compounds in addition to an ability to retain and separate organic compounds, a liquid chromatography column, and a method for producing a liquid chromatography column. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a schematic side view of a column according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view taken along line AA in FIG. [Diagram 3] FIG. 3 is a graph showing the pore distribution in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Preferred embodiments will be described below. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments.
[0023] <Column packing material> The column packing material of the present invention is made of porous glass beads having a breaking strength of 0.1 GPa or more and being substantially spherical. More specifically, the breaking strength is 0.1 GPa or more, preferably 0.2 GPa or more, 0.4 GPa or more, 0.6 GPa or more, and particularly 0.8 GPa or more. This allows a high pressure to be applied to the mobile phase (i.e., the flow rate of the mobile phase can be increased), enabling high-speed separation. The upper limit of the breaking strength is not particularly limited, but may be, for example, 5 GPa or less, particularly 3 GPa or less. In addition, since the porous glass beads are substantially spherical, it is easier to further increase the mechanical strength. In addition, the packing rate in the column housing can be increased, thereby improving the separation ability.
[0024] In the column packing of the present invention, the porous glass beads preferably contain SiO2 and ZrO2 as a glass composition, and more preferably contain, in mass %, 70-95% SiO2, more than 0-25% ZrO2, 0-10% Al2O3, and 0-10% B2O3+Na2O+K2O+CaO+P2O5+TiO2. The reason for limiting the glass composition in this way is explained below. In the following explanation, "%" means "mass %" unless otherwise specified.
[0025] SiO2 is the main component of the network-forming oxide in the porous glass beads. The SiO2 content is preferably 70 to 95%. More specifically, the lower limit of the SiO2 content is preferably 70% or more, 75% or more, 79% or more, 80% or more, and particularly preferably 81% or more. The upper limit of the SiO2 content is preferably 95% or less, 90% or less, and particularly preferably 85% or less. If the SiO2 content is too low, the weather resistance and mechanical strength of the porous glass beads tend to decrease.
[0026] ZrO2 is a component that develops the solid acidity of the porous glass beads and obtains the adsorption ability of organic compounds, and is a component that can obtain the adsorption ability for basic compounds in particular. It is also a component that can increase the mechanical strength of the porous glass beads. The content of ZrO2 is preferably more than 0 to 25%, and more preferably 10 to 25%. More specifically, the lower limit of the content of ZrO2 is preferably more than 0, 0.1% or more, 1% or more, 3% or more, 5% or more, 7% or more, 9% or more, 10% or more, and particularly preferably 10.1% or more. The upper limit of the content of ZrO2 is preferably 25% or less, and particularly preferably 20% or less. If the content of ZrO2 is too low, the above effect cannot be obtained. If the content of ZrO2 is too high, it becomes difficult to chemically bond octadecylsilyl groups (ODS groups) and trimethylsilyl groups (TMS groups) to the surface of the porous glass beads.
[0027] Al2O3 is a component that improves the weather resistance and mechanical strength of the porous glass beads. The content of Al2O3 is preferably 0 to 10%. More specifically, the lower limit of the content of Al2O3 is preferably 0% or more, 0.1% or more, 0.5% or more, and particularly preferably 1% or more. The upper limit of the content of Al2O3 is preferably 10% or less, and particularly preferably 5% or less.
[0028] From the viewpoint of improving the weather resistance and mechanical strength of the porous glass beads, it is preferable that B2O3+Na2O+K2O+CaO+P2O5+TiO2 (the total content of B2O3, Na2O, K2O, CaO, P2O5 and TiO2) is 0 to 10%. More specifically, it is preferable that the upper limit of the content of B2O3+Na2O+K2O+CaO+P2O5+TiO2 is 10% or less, 8% or less, and particularly 5% or less. The lower limit of the content of B2O3+Na2O+K2O+CaO+P2O5+TiO2 may be, for example, 0% or more, and particularly 0.1% or more. The preferred ranges of the contents of each of the components B2O3, Na2O, K2O, CaO, P2O5 and TiO2 are as follows:
[0029] The upper limit of the B2O3 content is preferably 10% or less, 8% or less, 5% or less, 3% or less, particularly preferably 1% or less. The lower limit of the B2O3 content may be, for example, 0% or more, particularly preferably 0.1% or more.
[0030] The upper limit of the Na2O content is preferably 10% or less, 8% or less, 5% or less, 3% or less, particularly preferably 1% or less. The lower limit of the Na2O content may be, for example, 0% or more, particularly preferably 0.1% or more.
[0031] The upper limit of the K2O content is preferably 10% or less, 8% or less, 5% or less, 3% or less, particularly preferably 1% or less. The lower limit of the K2O content may be, for example, 0% or more, particularly preferably 0.1% or more.
[0032] The upper limit of the content of RO (R is any one selected from Mg, Ca, Sr, and Ba) is preferably 10% or less, 8% or less, 5% or less, and particularly preferably 3% or less. The lower limit of the content of RO is, for example, preferably 0% or more, and particularly preferably 0.1% or more. When at least two or more components selected from MgO, CaO, SrO, and BaO are contained, the upper limit of their total content is preferably 10% or less, 8% or less, 5% or less, and particularly preferably 3% or less, and the lower limit of their total content is preferably 0% or more, and particularly preferably 0.1% or more.
[0033] The upper limit of the P2O5 content is preferably 10% or less, 8% or less, 5% or less, particularly preferably 3% or less. The lower limit of the P2O5 content may be, for example, 0% or more, particularly preferably 0.1% or more.
[0034] The upper limit of the TiO2 content is preferably 10% or less, 8% or less, 5% or less, particularly preferably 3% or less. The lower limit of the TiO2 content may be, for example, 0% or more, particularly 0.1% or more, and from the viewpoint of increasing the mechanical strength of the glass skeleton, the lower limit of the TiO2 content is preferably 0.1% or more.
[0035] In addition to the above components, the porous glass beads may contain Li2O, ZnO, La2O3, Ta2O5, TeO2, Nb2O5, Gd2O3, Y2O3, Eu2O3, Sb2O3, SnO2, Bi2O3, etc. in an amount of 10% or less, 5% or less, and particularly 3% or less each, or in a total amount of 20% or less.
[0036] In addition, since PbO is an environmentally hazardous substance, it is preferable that it is not substantially contained. Here, "substantially not contained" means that it is not intentionally contained as a raw material, and objectively refers to a content of less than 0.1%.
[0037] Average particle size of porous glass beads D 50 More specifically, the average particle diameter D 50 The lower limit of the average particle diameter D is preferably 0.1 μm or more, 0.3 μm or more, 0.5 μm or more, and particularly preferably 1 μm or more. 50 The upper limit of the average particle diameter D of the porous glass beads is preferably 300 μm or less, 100 μm or less, 30 μm or less, 20 μm or less, and particularly preferably 10 μm or less. 50 If the average particle diameter D of the porous glass beads is too small, the column pressure of the liquid chromatography column will be too high, making it difficult to use the beads as a column packing material. 50 If the average particle diameter D is too large, the theoretical plate number of the column will be significantly reduced, making it difficult to use as a column packing material. 50 (Volume-based average particle size) refers to a value measured by a laser diffraction scattering method. Specifically, it refers to the particle size at which the integrated amount is 50% cumulative from the smallest particle in the cumulative particle size distribution curve measured by the laser diffraction method. In the following explanation, the average particle size D 50 is sometimes expressed as "50% particle size."
[0038] The 10% particle size of the porous glass beads is preferably 0.01 to 300 μm, more preferably 0.1 to 100 μm. The 90% particle size of the porous glass beads is preferably 0.1 to 1000 μm, more preferably 1 to 500 μm. Here, the "10% particle size" refers to a particle size at which the cumulative amount is 10% from the smallest particle in a cumulative particle size distribution curve based on volume measured by a laser diffraction method. The "90% particle size" refers to a particle size at which the cumulative amount is 90% from the smallest particle in a cumulative particle size distribution curve based on volume measured by a laser diffraction method.
[0039] The pore diameter d (median value of pore distribution) of the porous glass beads is preferably 1 to 1000 nm. More specifically, the lower limit of the pore diameter d is preferably 1 nm or more, 3 nm or more, 10 nm or more, 11 nm or more, particularly 12 nm or more, and the upper limit of the pore diameter d is preferably 1000 nm or less, 500 nm or less, 100 nm or less, 80 nm or less, or 50 nm or less. If the pore diameter d is too small, it becomes difficult to separate polymer compounds. On the other hand, if the pore diameter d is too large, the specific surface area of the porous glass beads becomes small, and the separation ability of the column decreases, making it difficult to use them as a column packing material.
[0040] The specific surface area of porous glass beads is 10 to 800 m 2 More specifically, the lower limit of the specific surface area is preferably 10 m 2 / g or more, 30m 2 / g or more, 50m 2 / g or more, especially 100m 2 / g or more, and the upper limit of the specific surface area is 800 m 2 / g or less is preferable. If the specific surface area of the porous glass beads is too small, the retention, separation or adsorption capacity of the column is reduced, making it difficult to use them as a column packing material. If the specific surface area of the porous glass beads is too large, the retention, separation or adsorption capacity of the compound may be greater than the intended capacity.
[0041] Porous glass beads have a half-width Δd and mode diameter d in the pore distribution. m The ratio Δd / d m is preferably 0.55 or less, more preferably 0.5 or less, and even more preferably 0.4 or less. m The porous glass beads that satisfy the above value have a sharp pore distribution, and therefore can improve the separation characteristics of liquid chromatography columns. m The lower limit of is not particularly limited, but may be 0.01 or more, particularly 0.05 or more. m The preferred ranges are as follows:
[0042] The half-width Δd in the pore distribution of the porous glass beads is preferably 15 nm or less, particularly 10 nm or less. A small half-width Δd can improve the separation characteristics of a liquid chromatography column. The lower limit of the half-width Δd is not particularly limited, but may be 1 nm or more, particularly 2 nm or more.
[0043] Mode diameter d in the pore distribution of porous glass beads m is preferably 1 nm or more, 3 nm or more, 10 nm or more, 11 nm or more, particularly preferably 12 nm or more, and is preferably 1000 nm or less, 500 nm or less, 100 nm or less, 80 nm or less, 50 nm or less, particularly preferably 30 nm or less. m If is too small, it becomes difficult to separate polymer compounds. m If the specific surface area of the porous glass beads is too large, the retention, separation and adsorption capabilities of the column decrease, making it difficult to use the beads as a column packing material.
[0044] The column packing material is preferably such that at least a part of the inner pore surface of the porous glass beads is modified with a hydrophobic functional group. In other words, the column packing material preferably contains a hydrophobic functional group on the inner pore surface of the porous glass beads. In addition, the hydrophobic functional group is preferably an octadecylsilyl group (ODS group) and / or a trimethylsilyl group (TMS group).
[0045] The ODS conversion, which chemically bonds ODS groups to the porous glass beads, is preferably carried out by a toluene reflux method using dimethyloctadecylchlorosilane, octadecyltrichlorosilane, or the like. The porous glass beads can be used as a column packing for reversed-phase liquid chromatography, which separates compounds by utilizing hydrophobic interactions, by chemically modifying the inner pore surface with ODS groups. In addition, the porous glass beads after ODS conversion are preferably subjected to an end-capping treatment (secondary silylation) in which the remaining silanol groups are replaced with TMS groups. The end-capping treatment reduces the influence of secondary interactions caused by the remaining silanol groups, and the separation ability of the column can be improved. The end-capping treatment is preferably carried out by a toluene reflux method using, for example, trimethylchlorosilane, or the like. When the ODS conversion treatment and end-capping treatment are carried out on the porous glass beads, the column packing contains both ODS groups and TMS groups on the inner pore surface of the porous glass beads.
[0046] Thus, the column packing material of the present invention has the above-mentioned configuration, and thus has high mechanical strength, good pore characteristics, and solid acidity, and can have the adsorption ability for specific organic compounds in addition to the retention and separation ability of organic compounds. Therefore, the column packing material of the present invention is suitable as a column packing material for liquid chromatography that adsorbs specific organic compounds. In particular, the column packing material of the present invention is suitable as a column packing material for reversed-phase liquid chromatography that adsorbs specific organic compounds.
[0047] For example, the column packing material of the present invention preferably has an adsorption ability for basic compounds, such as pyrrolidine, piperidine, pyridine, bipyridine, ethylamine, diethylamine, triethylamine, histidine, and the like.
[0048] <Liquid chromatography columns> Fig. 1 is a schematic side view of a liquid chromatography column according to one embodiment of the present invention. Fig. 2 is a cross-sectional view taken along line AA in Fig. 1. As shown in Figs. 1 and 2, a liquid chromatography column 10 includes a column housing 1 and a column packing material 2 packed in the column housing 1. The column packing material 2 is made of the porous glass beads described above.
[0049] The column housing 1 is preferably cylindrical. The size of the column housing 1 is not particularly limited, but for example, the inner diameter is preferably 1 to 10 mm. From the viewpoint of suppressing a decrease in the separation ability of the column, the lower limit of the length of the column housing 1 is preferably 10 mm or more, 50 mm or more, and particularly preferably 100 mm or more. The upper limit of the length of the column housing 1 is not particularly limited, but from the viewpoint of easy handling, it may be 500 mm or less.
[0050] The column housing 1 is preferably made of a metal material, glass, or a resin material. For example, it is preferable to use stainless steel as the metal material. It is also preferable to use PEEK resin, acrylic resin, or fluororesin as the resin material. From the viewpoint of increasing the mechanical strength of the liquid chromatography column, it is preferable that the column housing 1 is made of a metal material.
[0051] The liquid chromatography column of the present invention includes the above-mentioned column packing material of the present invention, and therefore has high mechanical strength, good pore characteristics, and solid acidity, and can have an adsorption ability for specific organic compounds in addition to the retention and separation ability of organic compounds. In particular, the liquid chromatography column of the present invention is preferably used as a column for reversed-phase liquid chromatography. More specifically, the liquid chromatography column of the present invention can be suitably used for liquid chromatography that adsorbs specific organic compounds. In particular, the liquid chromatography column of the present invention can be suitably used for reversed-phase liquid chromatography that adsorbs specific organic compounds.
[0052] <Method of manufacturing liquid chromatography columns> The method for producing a liquid chromatography column of the present invention includes a precursor production step of obtaining precursor particles by pulverizing a glass base material, a porosity formation step of heat-treating the precursor particles to separate them into two phases and then removing one of the phases with an acid to obtain porous glass beads, a surface modification step of performing surface modification using a silane coupling agent, and a packing step of packing the porous glass beads into a column housing, the porous glass beads being characterized in that they have a breaking strength of 0.1 GPa or more and are approximately spherical in shape.
[0053] (Precursor preparation process) In the precursor preparation step, a glass base material is prepared and the glass base material is pulverized to obtain precursor particles (glass particles). First, glass raw materials are melted at 1300 to 1600°C for 2 to 12 hours. Next, the molten glass is molded to obtain a glass base material, and the glass base material is pulverized using a ball mill or the like to obtain precursor particles. After pulverization, classification is performed as necessary to obtain precursor particles having a desired average particle size. The obtained precursor particles are heated at 1000 to 3000°C using a burner or the like, and softened and fluidized to be spheroidized. As a result, precursor particles (glass particles) that are approximately spherical can be obtained. The glass base material preferably contains, for example, by mass%, 30 to 70% SiO2, more than 30 to 40% B2O3, 0 to 20% Li2O, 0 to 20% Na2O, 0 to 20% K2O, 50 to 10% P2O, more than 20 to 30% ZrO2, 0 to 20% Al2O3, and 0 to 20% RO (R is at least one selected from Mg, Ca, Sr, and Ba).
[0054] (Porous process) Next, the precursor particles are heat-treated to separate into two phases, and one of the phases is removed with acid to obtain porous glass beads. More specifically, the precursor particles are heat-treated to separate into two phases, a silica-rich phase and a boron oxide-rich phase (spinodal phase separation), and the boron oxide-rich phase is removed with acid to obtain porous glass beads. The obtained porous glass beads have a breaking strength of 0.1 GPa or more and are approximately spherical.
[0055] The heat treatment temperature of the precursor particles is preferably 500 to 800°C, particularly 600 to 780°C. If the heat treatment temperature is too high, the precursor particles may be softened and deformed. On the other hand, if the heat treatment temperature is too low, it is difficult to separate the precursor particles into phases. The heat treatment time is preferably 1 minute or more, 10 minutes or more, 30 minutes or more, particularly 1 hour or more. If the heat treatment time is too short, it is difficult to separate the precursor particles into phases. There is no particular upper limit to the heat treatment time, but since phase separation does not proceed beyond a certain level even if the heat treatment is performed for a long period of time, it is practically 180 hours or less.
[0056] When carrying out the heat treatment, it is preferable to mix inorganic nanoparticles with the precursor particles. This makes it possible to suppress fusion between the precursor particles. Examples of inorganic nanoparticles include alumina fine particles and zirconia fine particles, and it is particularly preferable to use alumina particles. Average particle diameter D of inorganic nanoparticles 50 The average particle size of the inorganic nanoparticles is preferably 1 to 100 nm, 5 to 50 nm, and particularly preferably 10 to 40 nm. If the average particle size of the inorganic nanoparticles is too small, they tend to aggregate and become difficult to handle. On the other hand, if the average particle size of the inorganic nanoparticles is too large, it becomes difficult to obtain the effect of suppressing fusion between the precursor particles.
[0057] The amount of inorganic nanoparticles added is preferably 0.5 parts by mass or more, 1 part by mass or more, particularly 2 parts by mass or more, relative to 100 parts by mass of the precursor particles. If the amount of inorganic nanoparticles added is too small, it is difficult to obtain the effect of suppressing the fusion of the precursor particles. In addition, when the average particle diameter of the precursor particles is small, the precursor particles tend to fuse together, so it is preferable to increase the amount of inorganic nanoparticles added. Specifically, the amount of inorganic nanoparticles added may be 5 parts by mass or more, 10 parts by mass or more, 20 parts by mass or more, particularly 25 parts by mass or more, relative to 100 parts by mass of the precursor particles. Although there is no particular limit to the upper limit of the amount of inorganic nanoparticles added, it is difficult to obtain further effects even if it is too large, so it is preferable to set the amount of inorganic nanoparticles added to 100 parts by mass or less, and even 80 parts by mass or less, relative to 100 parts by mass of the precursor particles.
[0058] In the step of phase-separating the precursor particles, a heterogeneous layer (a silica-rich layer containing approximately 80 mol% or more of silica) may be formed on the surface of the precursor particles. In this case, it is preferable to remove the heterogeneous layer by immersing the precursor particles in hydrofluoric acid for a short period of time (e.g., 1 second to 10 minutes).
[0059] Next, the precursor particles separated into two phases are immersed in an acid to remove the boron oxide-rich phase, thereby obtaining porous glass beads. As the acid, hydrochloric acid or nitric acid is preferably used, and these acids may be used in combination. The concentration of the acid is preferably 0.1 to 5 mol / L, particularly preferably 0.5 to 3 mol / L. The immersion time in the acid is preferably 0.1 hours or more, particularly preferably 0.2 hours or more. If the immersion time is too short, etching will be insufficient, making it difficult to obtain porous glass beads having the desired pore size, pore volume, or specific surface area. If the immersion time is too long, the precursor particles may dissolve in the acid, so the upper limit of the immersion time is preferably 20 hours or less, particularly preferably 10 hours or less. The immersion temperature is preferably 20°C or more, 25°C or more, particularly preferably 30°C or more. If the immersion temperature is too low, etching will be insufficient, making it difficult to obtain porous glass beads having the desired continuous pores. The upper limit of the immersion temperature is not particularly limited, but in reality, it is 99°C or less.
[0060] In addition, the precursor particles from which the boron oxide-rich phase has been removed with acid have a structure in which SiO2 gel and ZrO2 gel derived from the boron-rich phase are deposited in the pores. Therefore, in addition to the removal of the boron oxide-rich layer, it is preferable to perform additional etching with an acid solution and an alkaline solution. This allows the production of porous glass beads that reflect a phase-separated structure.
[0061] The ZrO2 gel can be removed, for example, by immersing the precursor particles in sulfuric acid. The concentration of sulfuric acid is preferably 0.1 to 5 mol / L, particularly 1 to 5 mol / L. The immersion time in sulfuric acid is preferably 0.1 hours or more, particularly 0.2 hours or more. If the immersion time is too short, it becomes difficult to remove the ZrO2 gel. There is no particular upper limit to the immersion time, but it is practically 20 hours or less, and further 10 hours or less. The immersion temperature is preferably 20°C or more, 25°C or more, particularly 30°C or more. If the immersion temperature is too low, it becomes difficult to remove the ZrO2 gel. There is no particular upper limit to the immersion temperature, but it is practically 99°C or less.
[0062] The SiO2 gel can be removed, for example, by immersing the precursor particles in an alkaline aqueous solution. As the alkaline aqueous solution, a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution, or the like can be used. These alkaline aqueous solutions may be mixed and used. The concentration of the alkaline solution is preferably 0.1 to 5 mol / L, particularly 0.5 to 3 mol / L. The immersion time in the alkaline aqueous solution is preferably 0.1 hours or more, particularly 0.2 hours or more. If the immersion time is too short, it becomes difficult to remove the SiO2 gel. There is no particular limit to the upper limit of the immersion time, but it is practically 20 hours or less, and further 10 hours or less. The immersion temperature is preferably 15°C or more, particularly 20°C or more. If the immersion temperature is too low, it becomes difficult to remove the SiO2 gel. There is no particular limit to the upper limit of the immersion temperature, but it is practically 99°C or less.
[0063] (Surface modification process) In the surface modification step, the surface is modified using a silane coupling agent. More specifically, it is preferable to dry the porous glass beads at a temperature of 100° C. or higher (for example, for 1 hour or more, particularly for 5 hours or more), and then use a silane coupling agent such as dimethyloctadecylchlorosilane or octadecyltrichlorosilane to chemically bond ODS groups to the surface of the porous glass beads under toluene reflux. It is also preferable to use pyridine as a catalyst in the ODS conversion. The reaction time for the ODS conversion is preferably 6 hours or more, particularly 12 hours or more. If the reaction time is too short, the ODS groups cannot be sufficiently introduced to the surface of the porous glass beads. There is no particular limit to the upper limit of the reaction time, but since once the introduction of the ODS groups has progressed to a certain extent, the ODS groups will not be chemically bonded to the surface of the porous glass beads even if the reaction is continued for a longer period, it is practically 48 hours or less.
[0064] After the reaction is completed, it is preferable to filter the porous glass beads from the reaction solution and wash the porous glass beads successively with toluene and methanol. By washing with toluene and methanol, reaction by-products such as pyridine hydrochloride and siloxane generated by the conversion of the porous glass beads to ODS can be removed.
[0065] It is preferable to further perform end-capping treatment on the ODS-modified porous glass beads. More specifically, it is preferable to perform end-capping treatment (secondary silylation) to replace the remaining silanol groups of the ODS-modified porous glass beads with TMS groups. The end-capping treatment is preferably performed under toluene reflux using trimethylchlorosilane as a silane coupling agent and pyridine as a catalyst after drying the ODS-modified porous glass beads at a temperature of 100° C. or higher (for example, 1 hour or more, particularly 5 hours or more). The reaction time of the end-capping treatment is preferably 6 hours or more, particularly 12 hours or more. If the reaction time is too short, the TMS groups cannot be sufficiently introduced on the surface of the porous glass beads. There is no particular limit to the upper limit of the reaction time, but since once the introduction of the TMS groups has progressed to a certain extent, the TMS groups will not chemically bond to the surface of the porous glass beads even if the reaction is continued for a longer period, the reaction time is practically 48 hours or less.
[0066] After the reaction is completed, it is preferable to filter the porous glass beads from the reaction solution and wash the porous glass beads with toluene and methanol in that order. By washing with toluene and methanol, by-products such as pyridine hydrochloride and siloxane generated by the conversion of the porous glass beads to TMS can be removed. In addition, from the viewpoint of reducing the remaining silanol groups on the inner pore surfaces of the porous glass beads, the above-mentioned capping treatment may be carried out two or more times.
[0067] (filling process) Finally, the resulting porous glass beads are packed into a column housing to produce a liquid chromatography column. EXAMPLES
[0068] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples.
[0069] Example 1: Porous Glass Beads Example 1 was produced by the following procedure. First, glass raw materials were placed in a platinum crucible so that the composition of the glass base material was, in mass%, SiO2 52.4%, Al2O3 2.6%, B2O3 17.5%, Na2O 5.2%, CaO 7.4%, ZrO2 11.0%, K2O 1.1%, P2O 50.8%, and TiO2 2.0%, and melted at 1500°C for 3 hours. When melting the glass raw materials, they were stirred using a platinum rod and homogenized. Next, the molten glass was formed into a film by pouring it out between a pair of cooling rollers. The obtained film-like glass was pulverized with a ball mill, and then classified with an air classifier to obtain precursor particles (glass particles) with an average particle size of 0.5 to 15 μm. The obtained precursor particles were fed into a furnace by a table feeder, and were softened and fluidized by heating at 1000 to 3000°C with an air burner to make the precursor particles spheroidized. The precursor particles were then further classified by elutriation. At this time, the 10% particle diameter D 10 is 3.2μm, 50% particle size D 50 is 4.1μm, 90% particle size D90 was 5.3 μm.
[0070] 25 parts by mass of alumina fine particles (manufactured by Aerosil Co., Ltd.) with an average particle size of several tens of nm were added to 100 parts by mass of the spherical precursor particles, and then heat-treated in an annealing furnace at 695°C for 10 hours to separate into two phases. In addition, the precursor particles after phase separation were immersed in hydrofluoric acid for 1 to 300 seconds to remove the heterogeneous layer (silica-rich phase) formed on the surface of the precursor particles. Etching with hydrofluoric acid was stopped by adding an aqueous solution of H3BO3 to neutralize the solution.
[0071] Next, the precursor particles from which the heterogeneous layer had been removed were immersed in acid to remove the boron oxide-rich phase. Specifically, the precursor particles were immersed in 1 mol / L nitric acid (96°C) for 0.5 to 5 hours, and then washed with ion-exchanged water. As an additional etching treatment, the precursor particles were immersed in 1.5 mol / L sulfuric acid (96°C) for 0.5 to 5 hours, and then washed with ion-exchanged water. The precursor particles were further immersed in a 0.5 mol / L aqueous sodium hydroxide solution (room temperature) for 0.5 to 5 hours, and then washed with ion-exchanged water. In this way, porous glass beads (Example 1) were obtained.
[0072] Observation of the obtained porous glass beads with FE-SEM (field emission scanning electron microscope, Hitachi SU-8220) showed that the beads had a porous structure based on spinodal phase separation. In addition, the composition of the obtained porous glass beads was analyzed with EDX (energy dispersive X-ray analyzer, Horiba EMAX Evolution EX-370 X-Max150). The results are shown in Table 1.
[0073] [Table 1]
[0074] (Comparative Example 1: Silica Gel Beads A) As Comparative Example 1, the average particle diameter D 50 Silica gel beads A having a diameter of about 5 μm were prepared.
[0075] For Example 1 and Comparative Example 1, the pore diameter d (median of the pore distribution), specific surface area, and pore distribution were measured using a pore distribution measuring device (QUARASORB SI manufactured by Anton Paar). In addition, the mode diameter d calculated from the pore distribution m and half-width Δd, half-width Δd and mode diameter d m The ratio Δd / d m The results are shown in Table 2. The pore distribution of the porous glass beads is shown in Figure 2.
[0076] [Table 2]
[0077] As shown in Table 2 and FIG. 2, the Δd / d m was smaller than that in Comparative Example 1, and the pore distribution was sharp.
[0078] The compression test was carried out using a microcompression tester (Shimadzu Corporation MCT-510). A flat indenter with a diameter of 20 mm was used, and the particle diameter d shown in Table 3 was measured at a loading speed of 1.1155 mN / sec. p A load was applied to one sample particle having the following properties. The test was carried out five times, and the load P [mN] and particle diameter d p The fracture strength Cs [GPa] was calculated from Equation 1 using the diameter [μm]. The average of five test results was also calculated. The fracture strength evaluation results are shown in Table 3.
[0079] [Formula 1] Cs = 2.48 × P / (π d p 2 )
[0080] [Table 3]
[0081] As shown in Table 3, the porous glass beads of Example 1 had a breaking strength about 18 times that of the silica gel beads A of Comparative Example 1.
[0082] (Example 1-2: ODS-modified porous glass beads) 1-10g of porous glass beads dried at 150℃ for 5-12 hours were dispersed in 20-200mL of dry toluene, 0.7-7g of dimethyloctadecylchlorosilane and 0.15-1.5mL of pyridine were added, and the mixture was heated under toluene reflux for 6-24 hours to produce ODS-modified porous glass beads. The ODS-modified porous glass beads were filtered out of the reaction solution, washed with toluene and methanol in that order, and dried at 120℃ for 5-12 hours.
[0083] Next, 1-10 g of ODS-modified porous glass beads were dispersed in 20-200 mL of dry toluene, 0.2-2 g of trimethylchlorosilane and 0.15-1.5 mL of pyridine were added, and the mixture was heated under toluene reflux for 6-24 hours to perform end-capping of the ODS-modified porous glass beads. The porous glass beads were filtered out of the reaction solution, washed with toluene and methanol in that order, and dried at 120°C for 5-12 hours.
[0084] The ODS-modified porous glass beads were packed into a column having an inner diameter of 2.1 mm and a length of 150 mm to prepare a column for liquid chromatography.
[0085] (Comparative Example 2-1: Silica gel beads B) As Comparative Example 2, a sol-gel method was used to produce a sintered body having a particle size of about 5 μm, a pore size of about 6 nm, and a specific surface area of 356 m. 2 / g of silica gel beads B were prepared.
[0086] (Comparative Example 2-2: ODS-modified silica gel beads B) 1-10 g of silica gel beads B dried at 150°C for 5-12 hours were dispersed in 20-200 mL of dry toluene, 1-10 g of dimethyloctadecylchlorosilane and 0.23-2.3 mL of pyridine were added, and the mixture was heated under toluene reflux for 6-24 hours to produce ODS-modified silica gel beads B. ODS-modified silica gel beads B were filtered out from the reaction solution, washed with toluene and methanol in that order, and dried at 120°C for 5-12 hours.
[0087] Next, 1-10 g of ODS-modified silica gel beads B were dispersed in 20-200 mL of dry toluene, and 0.3-3 g of trimethylchlorosilane and 0.23-2.3 mL of pyridine were added, followed by heating under toluene reflux for 6-24 hours to perform end-capping of ODS-modified silica gel beads B. The porous glass beads were filtered out of the reaction solution, washed with toluene and methanol in that order, and dried at 120°C for 5-12 hours.
[0088] The ODS-modified silica gel beads B were packed into a column having an inner diameter of 2.1 mm and a length of 150 mm to prepare a column for liquid chromatography.
[0089] (Evaluation of separation characteristics) The separation characteristics of the prepared liquid chromatography column were evaluated. The retention factor k' and separation factor α shown in Table 4 were measured and evaluated by an evaluation method called the Tanaka test. The flow rate of the mobile phase was 0.2 mL / min, the temperature was room temperature, detection was performed at UV 254 nm, and uracil was used as the non-retained compound.
[0090] [Table 4]
[0091] The retention coefficients k' of the compounds used in the Tanaka test are summarized in Table 5. In addition, the results of (1) hydrophobic retention, (2) hydrophobic selectivity, (3) stereoselectivity, and (4) hydrogen bond amount calculated based on Table 5 are shown in Table 6.
[0092] [Table 5]
[0093] [Table 6]
[0094] The (1) hydrophobic retention of the ODS-modified porous glass beads was 1.35, which was much lower than the 5.19 of the ODS-modified silica gel beads B. Therefore, the column using the ODS-modified porous glass beads had a smaller amount of alkyl chains in the entire column than the column using the ODS-modified silica gel beads B. This is because the specific surface area of the porous glass beads is smaller than that of the silica gel beads B. On the other hand, the evaluation results of (2) hydrophobic selectivity and (3) stereoselectivity were almost the same as those of the ODS-modified silica gel beads B. It is known that (2) hydrophobic selectivity increases as the coverage rate of the stationary phase surface by ODS groups and trimerylsilyl (TMS) groups increases. Therefore, the surface coverage rate by hydrophobic functional groups is about the same. In addition, (3) stereoselectivity was 1.42, which is higher than the result of the ODS-modified silica gel beads B. In general, when the ODS groups are closely present on the stationary phase surface, (3) stereoselectivity tends to increase. This is because triphenylene has a planar three-dimensional structure, and is sandwiched between the ODS groups, increasing retention, while o-terphenyl is less likely to enter between the ODS groups, decreasing retention. Therefore, it is considered that the ODS conversion of the porous glass beads has been performed appropriately. In addition, from the results of (2) hydrophobic selectivity and (3) stereoselectivity, it was found that liquid chromatography columns using ODS-modified porous glass beads have the same performance as ODS-modified silica gel beads in separating hydrophobic compounds.
[0095] (4) The amount of hydrogen bonds could not be measured in the ODS-modified porous glass beads. This is because the acidic compound phenol was separated from the non-retained compound uracil and eluted from the column, while the basic compound pyridine was adsorbed inside the column. On the other hand, in the liquid chromatography column using ODS-modified silica gel beads B, phenol and pyridine were separated and eluted, and the amount of hydrogen bonds (4) was 1.82. Therefore, it was found that the liquid chromatography column using ODS-modified porous glass beads has the property of adsorbing basic compounds such as pyridine.
[0096] (Evaluation of solid acidity) In order to investigate the reason why the porous glass had the ability to adsorb basic compounds such as pyridine, the solid acidity of the porous glass containing SiO2 and ZrO2 as main components was evaluated. First, a glass base material having the same composition as in Example 1 was processed into a plate shape with a thickness of 0.5 mm. Then, the glass base material was subjected to heat treatment in an electric furnace at 695°C for 12 hours to separate into two phases. The glass base material after phase separation was first immersed in hydrofluoric acid for several tens of seconds to several minutes to remove a heterogeneous layer on the surface of the glass base material. Next, the glass base material was immersed in 1.0 mol / L nitric acid (95°C) for 48 hours, and then washed with ion-exchanged water. Then, the glass base material was immersed in 1.5 mol / L sulfuric acid (95°C) for 48 hours, and then washed with ion-exchanged water. The glass base material was further immersed in 0.5 mol / L sodium hydroxide aqueous solution (room temperature) for 5 hours, and then washed with ion-exchanged water to obtain a porous glass plate. When the obtained porous glass plate was observed with FE-SEM, it had a porous structure based on spinodal phase separation. In addition, the composition of the obtained porous glass plate was analyzed using EDX and the composition was, in mass%, 83.3% SiO, 10.6% ZrO, 2.9% AlO, 0.1% NaO, 0.1% KO, 0.4% CaO, 51.6% PO, and 1.0% TiO. As in Example 1, the porous glass plate was a SiO-ZrO system porous glass containing 10.6% ZrO.
[0097] Next, the amount of ammonia desorption per specific surface area of the porous glass plate (i.e., a SiO-ZrO porous glass plate that was not surface-modified with ODS or TMS groups and contained 10.6% ZrO as in Example 1) was 0.745 μmol / m 2 Therefore, it was found that the porous glass plate had solid acid sites on the inner surfaces of the pores.
[0098] In addition, the pyridine adsorption FT-IR (an evaluation method that measures pyridine molecules adsorbed on a sample using Fourier transform infrared spectroscopy) of the porous glass plate was measured, and it was confirmed that the porous glass plate had Lewis acid sites and Brønsted acid sites.
[0099] The silica gel beads B of Comparative Example 2-1 (i.e., silica gel beads not surface-modified with ODS or TMS groups) were also evaluated for solid acid sites by ammonia temperature-programmed desorption (NH3-TPD). As a result, the detected value of the desorbed gas was below the quantifiable range of the calibration curve, so the amount of ammonia desorbed from the silica gel beads could not be calculated. Therefore, it is considered that the solid acid sites of the silica gel beads B are extremely few compared to the porous glass.
[0100] (summary) From the above, it is considered that the liquid chromatography column using the ODS-modified porous glass beads of Example 1-2 had the ability to adsorb basic compounds such as pyridine because there were many solid acid sites on the surface of the porous glass beads. In addition, the solid acid sites that are considered to have adsorbed basic compounds such as pyridine are acid sites derived from the porous glass beads. Therefore, the column packing material of the present invention can obtain a reversed-phase liquid chromatography column having the retention and separation ability of hydrophobic compounds and acidic compounds, and further the adsorption ability of basic compounds, without additionally introducing functional groups having the adsorption ability of basic compounds into the porous glass beads. [Industrial Applicability]
[0101] The column packing material of the present invention has high mechanical strength, good pore characteristics and solid acidity, and can be suitably used as a column packing material having an adsorption ability for specific organic compounds in addition to the retention and separation abilities of organic compounds, and as a column for liquid chromatography. [Explanation of symbols]
[0102] 1 Column housing 2 Column packing material 10 Liquid chromatography columns
Claims
1. A column packing material comprising approximately spherical porous glass beads having a breaking strength of 0.1 GPa or more.
2. The porous glass beads have a glass composition of SiO 2 and ZrO 2 The column packing material according to claim 1, comprising:
3. The porous glass beads have a glass composition, in mass %, of SiO 2 70-95%, ZrO 2 More than 0 to 25%, Al 2 O 3 0-10%, B 2 O 3 +Na 2 O+K 2 O+CaO+P 2 O 5 + TiO 2 The column packing material according to claim 1 or 2, containing 0 to 10%.
4. The porous glass beads have a glass composition, in mass %, of ZrO 2 The column packing material according to claim 1 or 2, containing 10 to 25%.
5. The average particle diameter D of the porous glass beads 50 3. The column packing material according to claim 1, wherein the pore size is 0.1 to 300 μm and the pore size is 1 to 1000 nm.
6. The specific surface area of the porous glass beads is 10 to 800 m 2 The column packing material according to claim 1 or 2, wherein the molecular weight is 1 / g.
7. The half-width Δd and mode diameter d in the pore distribution of the porous glass beads m The ratio Δd / d m The column packing material according to claim 1 or 2, wherein the σ is 0.55 or less.
8. 3. The column packing material according to claim 1, wherein at least a portion of the inner pore surface of the porous glass beads is modified with a hydrophobic functional group.
9. 9. The column packing material according to claim 8, wherein the hydrophobic functional group is an octadecylsilyl group and / or a trimethylsilyl group.
10. 3. The column packing material according to claim 1, which is for liquid chromatography.
11. A column for liquid chromatography comprising: a column housing; and the column packing material according to claim 1 or 2 packed in the column housing.
12. 12. The liquid chromatography column according to claim 11, which is a reverse phase liquid chromatography column.
13. A precursor preparation step of obtaining precursor particles by pulverizing a glass base material; a porosity forming step in which the precursor particles are heat-treated to separate them into two phases, and one of the phases is then removed with an acid to obtain porous glass beads; a surface modification step of performing surface modification using a silane coupling agent; a packing step of packing the porous glass beads into a column housing; Equipped with A method for producing a liquid chromatography column, wherein the porous glass beads have a breaking strength of 0.1 GPa or more and are approximately spherical.
Citation Information
Patent Citations
Porous glass particle and method for producing the same
JP2023026324A